THE EFFECT OF DZIKIR THERAPY ON SLEEP QUALITY OF COLLEGE STUDENTS AT SCHOOL OF NURSING UNIVERSITY OF JEMBER - Yulia Martha Fandiani; Wantiyah Wantiyah; Peni Perdani Juliningrum (NurseLine Journal, 2017)
Sleep quality is one of the physiological needs of life. Poor sleep quality can affect college student performance. One of sleep quality management is dzikir therapy. Dzikir therapy is a complementary therapy that uses mind-body technique therapy. This research aimed to identify the effect of dzikir therapy on sleep quality of college students at School of Nursing University of Jember. This research used quasy experimental with control group pretest-posttest design. The sampling technique was purposive sampling involving 34 respondents divided into 17 respondents as dzikir therapy group and 17 respondents as control group. The instrument used Pittsburgh Sleep Quality Index questionnaire (PSQI). Data were analyzed using dependent t-test and independent t-test with significance level of 95 % (α=0.05). The results showed that there was a significant difference of sleep quality score before and after dzikir therapy with the average decreased from 8.59 to 4.35 (p= 0.001). Meanwhile, there was no significant difference in sleep quality score between pretest and posttest of control group with the average decreased from 7.94 to 7.53 (p= 0.150). For both group, sleep quality of students decreased, but the decrease in the intervention group was higher than in control group. So, there was a significant difference of sleep quality score between intervention group and control group (p=0.001). Relaxation effect of dzikir therapy stimulates the hypothalamus to affect the pineal gland in producing melatonin which make it easy to sleep. The conclusion is there is a significant effect of dzikir therapy toward sleep quality of college students at School of Nursing University of Jember. Nurses can apply dzikir therapy to increase sleep quality of clients, besides dzikir therapy can also be a part of activity for college students before sleeping.